PENGARUH CITRA SEKOLAH DAN KUALITAS LAYANAN PENDIDIKAN MELALUI PERILAKU WALI MURID TERHADAP KEPUTUSAN MEMILIH SEKOLAH MENENGAH PERTAMA ISLAM TERPADU IMAM SYAFII 2 KOTA PEKANBARU - Adiputra Maulana Tareq; Rahayu Danar Deny; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of School Image and Quality Of EducationServices through Parents Behavior on the Choosing Decision the Imam Syafii 2Integrated Islamic Junior High School Pekanbaru City. The population in thisstudy includes the Parents who send their children to SMP IT Imam Syafii 2Pekanbaru City, where the total number of students is 219, so the researchrespondents in this case are the Parents totaling 219. Determination of the sampleis done using probability sampling method. In this study, the sample studied useda questionnaire as an instrument to prove the results of the study, for hypothesistesting in this study using the path analysis method (path analysis) and processedusing SPSS Statistics 18 software. The results of the study show that: 1) there is asignificant effect of School Image on Behavior, 2) there is a significant influenceon the Quality Of Education Services on Behavior, 3) there is a significantinfluence on School Image on Choosing Decisions, 4) there is a significantinfluence on the Quality Of Education Services on the Choosing Decisions, 5)there is a significant influence of Behavior on the Choosing Decisions, 6) there isa significant influence of School Image on the Choosing Decisions throughBehavior, and 7) there is a significant influence on the Quality of EducationalServices on the Choosing Decisions through Behavior.Keywords : School Image, Quality of Educational Services, Behavior, ChoosingDecision.